2004
DOI: 10.1111/j.1460-2695.2004.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

The role and effects of the third body in the wheel–rail interaction

Abstract: A B S T R A C T This paper focuses on the presence of the third body, a solid interfacial layer in the wheelrail contact. This third body is studied from different viewpoints: its presence including composition, thickness and morphology; and its role with respect to its load-carrying capacity, shearing behaviour, transfer of material and finally global friction coefficient. The general approach is phenomenological and is carried out as closely as possible of the real tribological behaviour of this contact. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Previous work has focused on the study of the "natural" third body between the wheel and rail to explain the interfacial friction and adhesion behavior based on the composition of the third body layer [12]. However, more recently, researchers have begun to investigate the creation of an "engineered" third body layer as a means of controlling friction at the wheel/rail interface, especially between the wheel tread and rail head [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has focused on the study of the "natural" third body between the wheel and rail to explain the interfacial friction and adhesion behavior based on the composition of the third body layer [12]. However, more recently, researchers have begun to investigate the creation of an "engineered" third body layer as a means of controlling friction at the wheel/rail interface, especially between the wheel tread and rail head [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the tests with FMs, it may be possible that the firm adherence of the third body layer on the wheel disk (rather than on both disks) could also have influenced the different work-hardening between wheel and rail. Berthier et al [20] showed that a third body layer present between wheel and rail surfaces can accommodate their relative displacement (or slip) so that the shearing of the near-surface grains of wheel and rail surfaces is decreased, thus reducing the work-hardening effect.…”
Section: Fig 14 Sub-surface Micro-photographs Of the Cross Section mentioning
confidence: 99%
“…Although the concept of a TB is sometimes employed in a rather general context that also includes liquids or layers of deformable media (see, e.g. Berthier et al [1]), in this work a TB explicitly refers to solid continua of a granular nature without interstitial fluid layers (i.e. dry granular media).…”
Section: Contact Interfaces With Third Bodiesmentioning
confidence: 99%
“…For instance, in biomechanical applications where knee and hip implant surface degradation is of concern, the analysis may include both wear debris within the joint [10] and cement particle contaminants from the implant-bone interface [11]. Similarly, wheel-rail traction investigations involve both a wear process that generates intrinsic TBs [12] and a layer of contaminant material on the rail [1]. Extrinsic TBs are almost always undesirable.…”
Section: Contact Interfaces With Third Bodiesmentioning
confidence: 99%